Spiral-based data dissemination in sensor networks. (7th December 2006) - Sun, Yang; Fan, Guangbin; Chen, Shigang
Data dissemination is a key problem that bottlenecks the wide application of Wireless Sensor Network (WSN). In this paper, a novel data dissemination scheme - Logarithmic Spiral Data Dissemination (LSDD) - is proposed. In LSDD, data advertisements are disseminated following a spiral-like path, which involve only a small fraction of nodes in a sensor network. By exploiting nice features of spiral, this scheme scales well for large sensor networks while prolonging the network lifetime. In numerical analysis and simulations, we show the distinct merits of LSDD as follows: lower dissemination cost (O√n) compared to that of flooding-based schemes (O(n)), controllable topology by spiral parameters, excellent scalability, and good fault tolerance. We evaluate the extra delay caused by LSDD as a trade-off for its advantages, which is shown to be within a tolerable range.